2014
DOI: 10.1080/02673843.2014.963630
|View full text |Cite
|
Sign up to set email alerts
|

Differential social evaluation of pregnant teens, teen mothers and teen fathers by university students

Abstract: Youth may be particularly attuned to social evaluation during the teen years with implications for physical and mental health. Negative attitudes and stereotypes constitute an important type of social evaluative threat. Pregnant and parenting teens not only encounter challenges associated with their early transition to parenthood, but also are confronted with unfavourable attitudes of others. A university sample of 255 men and women responded to surveys targeting their feelings and beliefs about pregnant teens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
3
21
1
Order By: Relevance
“…This is possibly because mothers have to physically carry the child, and also because society often judges women more harshly surrounding the topic of sexuality (Carpenter, 2005). This finding is significant as it is in contrast with findings in a majority white and black population which found that teen mothers were perceived more positively than teen fathers (Weed & Nicholson, 2015). The disparity in judgment emphasizes the need for additional support during pregnancy, especially for teen mothers, as negative stigmatization can interfere with both mother and child well-being (SmithBattle, 2013; Somerville, 2013).…”
Section: Discussioncontrasting
confidence: 95%
“…This is possibly because mothers have to physically carry the child, and also because society often judges women more harshly surrounding the topic of sexuality (Carpenter, 2005). This finding is significant as it is in contrast with findings in a majority white and black population which found that teen mothers were perceived more positively than teen fathers (Weed & Nicholson, 2015). The disparity in judgment emphasizes the need for additional support during pregnancy, especially for teen mothers, as negative stigmatization can interfere with both mother and child well-being (SmithBattle, 2013; Somerville, 2013).…”
Section: Discussioncontrasting
confidence: 95%
“…Adolescent mothers were perceived as having less positive internal and parenting characteristics and more anti‐social behaviour than adult mothers. Compared to adult mothers, they were perceived less favourably across all domains; a finding consistent with attitudes in the United States (Weed & Nicholson, ). Further, participants expressed less positive emotions towards adolescent mothers, though there were no differences for negative emotions.…”
Section: Discussionsupporting
confidence: 69%
“…Overall evaluations of the target mother were measured using a feelings thermometer. Participants rated their feelings towards the target on a scale from 0 (very cold/unfavourable) to 100 (very warm/favourable; Weed & Nicholson, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations